Microsatellites assisted rapid identification of mandarin hybrids and assessment of their phenotypic variability - KAUR, KIRANDEEP; KUMAR, KRISHAN; KAUR, KAMALJIT; ARORA, PARSHOTAM KUMAR; SINGH, KULDEEP (The Indian Journal of Agricultural Sciences, 2021)
Kinnow (Citrus nobilis × C. deliciosa) is a commercially important mandarin but contains large number of seeds. Mukaku Kishu (C. kinokuni), a seedless mandarin can be used to transfer seedlessness in Kinnow through hybridization. But, the polyembryony in Kinnow and absence of any heritable morphological trait in Mukaku Kishu are limiting factors in early identification of hybrids. SSR markers due to their high polymorphism and co-dominant nature are useful for hybrid identification. We performed hybridization between Kinnow (♀) and Mukaku Kishu (♂) and differentiated hybrids using SSR markers. A total of 134 SSR markers were tested for polymorphism between the parents; 20 were found polymorphic while four (CMS04, Ci06A05b, CiBE1500 and TAA15) were suitable for hybrid detection. The hybrid detection ability varied among the markers. The marker CMS04 identified 67 hybrids while the remaining three markers independently identified 104 hybrids from the total analysed 697 seedlings. The hybrid seedlings differed for height and number of spines per plant. The two traits also showed moderate positive association (Pearson correlation = 0.69). The study demonstrated the practical utility of SSR markers in enhancing the efficiency of breeding programmes in absence of distinct morphological distinguishers for hybrid detection. The identified hybrids progeny will serve as a foundation for identification of potentially seedless candidates.